Characterization and testing of materials for nuclear reactors: Proceedings of a technical meeting held in Vienna, May 29--June 2, 2006 - Paranjpe, Shriniwas K (International Atomic Energy Agency, 2013)
Industrial growth, energy consumption are seen as measures towards economic developments. With increase in industrial development worldwide, the demand of energy is continually on the rise. Today, the energy industry is facing many challenges. Nuclear fission and nuclear fusion are seen as important future energy sources. Development of innovative reactor designs with large efficiency for fuel burn up is one of the needs of fission reactors. The materials resistant to high dose of radiations in fusion reactors is another major challenge. The production of electricity without global warming is an important pressing demand on the energy sector. The demands on quality control of components for nuclear and heavy industry are very stringent. Development of well characterized, high quality materials is therefore essential for safe, efficient and reliable operation of engineering components. The diagnosis of failure of machinery parts comes from the post operational characterization of materials. Various destructive and non-destructive techniques are used for this purpose. Research reactors have played an important role in non-destructive characterization of materials and have contributed to technology development. This publication focuses on characterization of materials for industries in general and nuclear energy sector in particular. The main focus is on research reactor based techniques with some discussion on other allied methods like positron annihilation.--Publisher's description.